Minha narrativa, eu mesma requadro : a história das HQs midiativistas e a representatividade de Marielle em HQ - Conceição, Suzana Rosa Ataide da (2023)
This work investigates comics as a viable tool for sharing activist ideas about diversities and problems rooted in the social structure. The research also questions whether comics are a communication power capable of expanding scientific knowledge in a practical and accessible way. To achieve this purpose, it analyzes intersectionally (GONZALEZ, 2020; AKOTIRENE, 2017 and CARRERA 2021a and 2021b) and through the very language of comics (EISNER, 1985 and MCCLOUD, 2005) the biographical comic book “Marielle Franco Raízes” (Instituto Marielle Franco , 2021). The work shows the history of comics (RAHDE, 1996; ROBBINS, 2001; and ALMEIDA, CRUZ and HORN, 2011) and their relationship with the mediactivism (BRAIGHI, 2028) to verify if the format can help black women in the control of their images (BUENO, 2020), their representations (HALL, 2016 and hooks, 2019) and representativeness. In its chapters of analysis and final considerations, using the format of comics, the research presents the importance of self-representation in images and texts to drive black women, and other oppressed populations, to occupy spaces and fight for their ideals.